Improvement in upconversion/downshifting luminescence of Gd2O3 :Ho3+/Yb3+ phosphor through Ca2+ / Zn2+ incorporation and optical thermometry studies. (April 2019) - Kumar, Abhishek; da Silva, Joaquim C.G. Esteves; Kumar, Kaushal; Swart, Hendrik C.; Maurya, Sachin K.; Kumar, Promod; Tiwari, Surya P.
Graphical abstract: Highlights: Synthesis and upconversion/downshifting emission analysis of Gd2 O3 :Ho 3+ /Yb 3+ nanoparticle has been done. Further, the incorporation of Ca 2+ /Zn 2+ concentration variation on different parameters of present sample have been studied. The paramagnetic ability of present samples has been studied for possibility of biomedical applications of present sample. The temperature sensing ability of present samples have also been studied comparatively. Abstract: The Ho 3+ /Yb 3+ doped Gd2 O3 phosphor was synthesized via the hydrothermal process. Co-doping of Ca 2+ and Zn 2+ ions caused a change in the particle morphology and aggregation of the Ho 3+ /Yb 3+ : Gd2 O3 phosphor. The structural characterization of these particles was performed using X-ray diffraction analysis, Fourier transforms infrared spectroscopy and scanning electron microscopy. The 980 nm excitation assisted upconversion luminescence and 449 nm excitation assisted downshifting luminescence of these phosphor particles were compared through the incorporation of Ca 2+ and Zn 2+ co-dopants. The co-dopants concentration was varied at 0, 5, 10, 15 and 20 mol %. The change in upconversion/downshifting luminescence under the influence of the optimized molar concentration of these co-dopants was studied and explained based on structural variations in the present phosphor material. The paramagnetic behavior of these particles was characterized and compared to search possible applications of these particles in the biomedical field. The samples were studied comparatively for temperature sensing.